2018
DOI: 10.2494/photopolymer.31.169
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Charge Accumulation States in Polymer Solar Cells using Light-Induced Electron Spin Resonance Spectroscopy

Abstract: Charge accumulation states in organic solar cells were studied in detail by a microscopic characterization with light-induced electron spin resonance (ESR) spectroscopy during device operation using a typical polymer solar cell of indium-tin oxide (ITO)/poly (3,4-ethylenedioxythiophene):poly (4-styrenesulfonate) (PEDOT:PSS)/regioregular poly(3-hexylthiophene) (P3HT):fullerene [6,6]-phenyl C 61 -butyric acid methyl ester (PCBM)/LiF/Al. Two light-induced ESR signals with a narrow and broad linewidth were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 27 publications
4
26
0
Order By: Relevance
“…Particularly, the EDMR line shape was unchanged between the cases of the film orientation perpendicular and parallel to the static field. This result suggests that the signal arises from spin species in the random chain orientation, consistent with the previous references that suggested the signals originating from hole carriers on P3HT chains with random orientation. The narrow component is, thus, contributed by the hole carrier, meaning that the broad component could be contributed by electron carriers. Concerning the line width, in a recent report on polymer LEDs, the spectral component from a hole of the EDMR signal was suggested to give a narrower spectrum in the double-Gaussian model.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Particularly, the EDMR line shape was unchanged between the cases of the film orientation perpendicular and parallel to the static field. This result suggests that the signal arises from spin species in the random chain orientation, consistent with the previous references that suggested the signals originating from hole carriers on P3HT chains with random orientation. The narrow component is, thus, contributed by the hole carrier, meaning that the broad component could be contributed by electron carriers. Concerning the line width, in a recent report on polymer LEDs, the spectral component from a hole of the EDMR signal was suggested to give a narrower spectrum in the double-Gaussian model.…”
Section: Resultssupporting
confidence: 89%
“…We here discuss the ESR parameters obtained from the double-Gaussian model. First, the g -value of the narrow component (2.0020) coincides with the g -values of hole carriers of P3HT determined by ESR for solar cells and is close to the g -center value (2.0018) of an iodine-doped spin-coated P3HT film determined by W-band ESR spectroscopy . Particularly, the EDMR line shape was unchanged between the cases of the film orientation perpendicular and parallel to the static field.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The estimated B 1/2 values for C n and C b are 0.17 and 0.60 mT, respectively, which are broader than those estimated from the 179 MHz EDMR spectrum. Because the estimated g -factor for the C n component is close to that of holes in P3HT, the C n and C b components are attributed to the ESR of holes and electrons, respectively …”
Section: Resultsmentioning
confidence: 90%
“…In this mode, carriers can be stored in the interface between insulator and semiconductor until the linearly increasing voltage is applied. Additionally, it is reported that light-induced electron spin resonance (ESR) spectroscopy can contribute to the analysis of charge accumulation states [ 41 ].…”
Section: Introductionmentioning
confidence: 99%